Shifting Dynamics: Modernization and Its Impact on Dalit Occupations - Silwal, Keshab Raj (DMC Journal, 2024)
This article explores the modernization of traditional Dalit occupations and their compatibility and competition in the market. It discusses how traditional Dalit occupations, once limited by outdated technologies, were insufficient to sustain their livelihoods.As societal dynamics shift with modernization and urbanization, opportunities for education and diverse occupations emerge (Rostow, 1959, Hochschild,1989; Ritzer, 2011), influencing traditional occupations. Focusing on Godawari Municipality, Ward No. 5, this study employs random sampling and an explanatory method to analyze data. The findings reveal a noteworthy departure from traditional Dalit occupations such as metalwork, leatherwork, and sewing. Modernization and urbanization have not only provided educational opportunities for Dalits but also influenced their traditional occupations. The study indicates that Dalits, particularly the younger generation, are opting for new occupations aligned with their education. The increased educational levels among Dalits are instrumental in their pursuit of alternative professions, driven by aspirations for higher income and improved living standards. This shift is a strategic response to the desire to educate their children and meet daily needs more easily. Notably, Dalits are modernizing their traditional occupations by incorporating new technologies and establishing shops in market areas. This transformative shift is not limited to traditional sectors; more Dalits are now entering the business and the service industry. The article emphasizes the interaction between modernization, urbanization, and the occupational choices of Dalits, highlighting their active adaptation to evolving socio-economic conditions.